CYTOTOXICITY OF COLCHICINE DERIVATIVES IN PRIMARY CULTURES OF HUMAN HEPATOCYTES - Dvorak, Zdenek; Ulrichova, Jitka; Weyhenmeyer, Roland; Simanek, Vilim (Biomedical papers, 2007)
Background: Colchicine has been used to treat gout for centuries. However, owing to its toxicity it displays a variety of side effects. The replacement of colchicine by less toxic but still active derivatives would solve this drawback.Aim: The aim of this study was to examine the cytotoxicity of 17 colchicine derivatives.Methods: Primary cultures of human hepatocytes were the model of choice. Prior to testing, we measured the biochemical parameters of liver donors and the toxicological response of the hepatocytes cultures. For toxicity testing, cells were treated for 24 h with tested compounds in concentrations 1-100 µM. We monitored lactate dehydrogenase (LDH) leakage into the medium, mitochondrial activity (MTT test) and secretion of albumin.Results: Our data show that LDH and MTT were less sensitive parameters compared to albumin secretion for monitoring the toxicity of colchicine derivatives. Compounds with lower antimitotic activity displayed lowered toxicity.Conclusion: Since human hepatocytes in culture are quiescent cells, they are not as susceptible to tropolone alkaloids as proliferating cells. Screening for colchicine derivatives with lowered cytotoxicity revealed that 10-O-demethylated compounds might be the substances of choice.
Keywords: Colchicine derivatives/Toxicity/Human hepatocytes